Exposure to maternal obesity during suckling outweighs in utero exposure in programming for post-weaning adiposity and insulin resistance in rats - Grace George (Nature Portfolio, 2019)
Abstract Exposure to maternal obesity during early development programmes adverse metabolic health in rodent offspring. We assessed the relative contributions of obesity during pregnancy and suckling on metabolic health post-weaning. Wistar rat offspring exposed to control (C) or cafeteria diet (O) during pregnancy were cross-fostered to dams on the same (CC, OO) or alternate diet during suckling (CO, OC) and weaned onto standard chow. Measures of offspring metabolic health included growth, adipose tissue mass, and 12-week glucose and insulin concentrations during an intraperitoneal glucose tolerance test (ipGTT). Exposure to maternal obesity during lactation was a driver for reduced offspring weight post-weaning, higher fasting blood glucose concentrations and greater gonadal adiposity (in females). Males displayed insulin resistance, through slower glucose clearance despite normal circulating insulin and lower mRNA expression of PIK3R1 and PIK3CB in gonadal fat and liver respectively. In contrast, maternal obesity during pregnancy up-regulated the insulin signalling genes IRS2, PIK3CB and SREBP1-c in skeletal muscle and perirenal fat, favouring insulin sensitivity. In conclusion exposure to maternal obesity during lactation programmes offspring adiposity and insulin resistance, overriding exposure to an optimal nutritional environment in utero, which cannot be alleviated by a nutritionally balanced post-weaning diet.